2018
DOI: 10.1111/jofo.12240
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term monitoring of Yellow‐naped Amazons ( Amazona auropalliata ) in Costa Rica: breeding biology, duetting, and the negative impact of poaching

Abstract: The population of Yellow-naped Amazons (Amazona auropalliata) declined by an estimated 50% between 1980 and 2000, and the current population is estimated to be between 10,000 and 50,000. Poaching of young has been a persistent problem, but the species is also threatened by habitat loss and degradation. Because most aspects of their life history, behavior, and ecology have not been examined in wild populations, we studied Yellow-naped Amazons with the following objectives: (1) identify the species of trees used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
(48 reference statements)
0
12
0
1
Order By: Relevance
“…While our observations suggest this is often the case, this estimate is best viewed as a theoretical best estimate of reproductive success. Our own data on nesting success from nest monitoring conducted from 1999 to 2008 in some of the same Costa Rican populations surveyed here found that only 11% of nests successfully fledged young, with most of the mortality arising from nest poaching (Dahlin et al 2018). Nesting success is higher in populations of the sister species the Yellow-headed Amazon, Amazona oratrix, where 49 of 155 (31%) of nests monitored within or adjacent to protected areas over two nesting seasons from 2016-2017 successfully fledged young, but only limited roost surveys have been conducted in these populations due to an absence of stable roosting sites (C. Britt unpubl.…”
Section: Population Trendsmentioning
confidence: 58%
See 2 more Smart Citations
“…While our observations suggest this is often the case, this estimate is best viewed as a theoretical best estimate of reproductive success. Our own data on nesting success from nest monitoring conducted from 1999 to 2008 in some of the same Costa Rican populations surveyed here found that only 11% of nests successfully fledged young, with most of the mortality arising from nest poaching (Dahlin et al 2018). Nesting success is higher in populations of the sister species the Yellow-headed Amazon, Amazona oratrix, where 49 of 155 (31%) of nests monitored within or adjacent to protected areas over two nesting seasons from 2016-2017 successfully fledged young, but only limited roost surveys have been conducted in these populations due to an absence of stable roosting sites (C. Britt unpubl.…”
Section: Population Trendsmentioning
confidence: 58%
“…Yellow-naped Amazons appear quite tolerant of low-level disturbance; in our surveys most roosts were found in secondary deciduous forest, and many were in close proximity to human habitation; we actually found that mean roost size was larger for roosts located within 100 m of human habitation than for those located farther away. Furthermore, our observations suggest that Yellow-naped Amazons are capable of, and may actually prefer, to nest in more open landscapes such as those maintained by cattle ranching or controlled burns (Dahlin et al 2018). Thus it is not human activity in general, but rather specific forms of human activity that are driving the observed declines in the Yellow-naped Amazon.…”
Section: Factors Contributing To Declinementioning
confidence: 76%
See 1 more Smart Citation
“…Other parrot species are reported to breed in palm snags in their native ranges (Berkunsky et al 2014;Dahlin et al 2018). Amazona parrots are increasing in population and expanding their range in the southern United States, particularly Florida and California, where palm trees are common (Mori et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings at this site show an encouraging and positive trend, unlike that found for many other psittacines. For example, the population of yellow-naped parrots Amazona auropalliata has declined by nearly 50% since 1980 because many of these birds are caught illegally for the pet trade (Dahlin et al 2018). Marsden & Royle (2015) carried out a survey of density and abundance changes among 356 parrot species.…”
Section: Hyacinth Macaw Population At the São Francisco Do Perigara Rmentioning
confidence: 99%